Jan Terje Faarlund: The Syntax of Mainland Scandinavian - Engdahl, Elisabet (Norsk Lingvistisk Tidsskrift, 2020)
With the publication of this book, Jan Terje Faarlund, professor emeritus of Scandinavian Linguistics at the University of Oslo, makes a comparative overview of Danish, Norwegian and Swedish available to linguists who are unable to read these languages. I believe this is the first book of its kind. To find a similar attempt we have to go back to the 1940s when Lage Hulthén published his comprehensive comparison of the syntax of Nordic languages, see Hulthén (1944, 1947). Hulthén’s study is however written in Swedish and is based on written sources mainly from the end of the 19th century and the beginning of the 20th. The main sources for Faarlund’s book are the three reference grammars published in Norwegian, Swedish and Danish between 1997 and 2011: Norsk referansegrammatikk (Faarlund, Lie & Vannebo, 1997, abbreviated NRG), Svenska Akademiens grammatik (Teleman, Hellberg & Andersson 1999, abbreviated SAG) and Grammatik over det Danske Sprog (Hansen & Heltoft 2011, abbreviated GDS). These grammars are accessible to linguists who speak any one of the described languages, whereas the primary intended readership for Faarlund’s new book is presumably the linguistic community outside Scandinavia. This is also the reason why this review is written in English.